2022
DOI: 10.5334/irsp.613
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Structural Validity of Stereotype Content Scales – A Preregistered Re-Analysis of Published Data and Discussion of Possible Future Directions

Abstract: The Stereotype Content Model (SCM) plays a prominent role in social perception research when comparing the evaluation of different targets on warmth and competence dimensions. However, there is scarce information on the SCM's measurement properties. Thus, in this article, we provide a comprehensive test of the SCM's structural validity (i.e., reliability, dimensionality, cross-group comparability of measurement properties). We re-analysed published SCM data from English speaking participants (study 1: 78 datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 63 publications
(123 reference statements)
1
26
0
Order By: Relevance
“…We aim to advance the research on occupational stereotypes and the SCM in two important ways: First, by addressing methodological critiques directed toward the SCM scales through the development of a context-specific warmth and competence measure, the examination of the SCM's dimensionality, and the application of advanced analytical approaches for mean value comparison that guarantee measurement invariance as a precondition for the valid interpretation of results (Asparouhov & Muthén, 2014;Friehs et al, 2022;Kotzur et al, 2019).…”
Section: The Present Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…We aim to advance the research on occupational stereotypes and the SCM in two important ways: First, by addressing methodological critiques directed toward the SCM scales through the development of a context-specific warmth and competence measure, the examination of the SCM's dimensionality, and the application of advanced analytical approaches for mean value comparison that guarantee measurement invariance as a precondition for the valid interpretation of results (Asparouhov & Muthén, 2014;Friehs et al, 2022;Kotzur et al, 2019).…”
Section: The Present Researchmentioning
confidence: 99%
“…Previous research has found German and English SCM scales to perform poorly in confirmatory factor analyses and measurement invariance assessments (indicating that the dimensionality of warmth and competence was not given and that (latent) mean-value comparisons were biased; Friehs et al, 2022;Kotzur et al, 2019Kotzur et al, , 2020. Consequently, we developed a new SCM scale with a specific focus on assessing the warmth and competence of occupational groups.…”
Section: Stereotype Contentmentioning
confidence: 99%
See 3 more Smart Citations